Knowledge of the concept of corporate social responsibility in agribusiness enterprises (based on the example of the SME sector in Malopolska) = Znajomość koncepcji społecznej odpowiedzialności w przedsiębiorstwach agrobiznesu (na przykładzie sektora MSP z Małopolski) - Ratajczak, Marcin (Zielona Góra: Faculty of Economics and Management Press)
Corporate Social Responsibility (CSR) initiative in Poland is relatively little known and has not been yet deeply rooted in the consciousness of Polish entrepreneurs especially in the field of SMEs and local communities. CSR is a concept whereby companies at the stage of strategy building voluntarily take into account the social interests and environmental protection, as well as relationships with their stakeholders. Therefore, the aim of this paper is to present issues related to the knowledge of the CSR concept in the surveyed agribusiness enterprises.
Keywords: koncepcja społecznej odpowiedzialności; agrobiznes; sektor MŚP; znajomość CSR; concept of corporate social responsibility; agribusiness; SME sector; knowledge about CSR